Fishery, systematics and stock dynamics of billfishes landed along the Indian coast: Stock dynamics of billfishes - S. Surya; R. Prathibha; E. M. Abdusammad; T. L. Asha; B. Santhosh; B. B. Nayak; N. S. Jeena; K. G. Mini; Shubhadeep Ghosh; J. H. Kingsly; P. Abdul Azeez; C. Anulekshmi; et al. (Indian Journal of Fisheries, 2023)
Sailfishes, marlins, spearfishes and swordfishes commonly referred to as billfishes are highly migratory species, with a worldwide distribution in tropical and subtropical oceans. The landings of billfishes along the Indian coast registered an increasing trend with an estimated landing of 14,759 t in 2019. Kerala (41%) contributed the maximum followed by Tamil Nadu (28%), Andhra Pradesh (18%), Gujarat (8%) and Maharashtra (2%) to the total billfish landings during the last decade. Mechanised gillnetter cum hook and line was the major gear landing billfishes. The major species landed during 2012-2019 were Istiophorus platypterus (52.2%), Istiompax indica (21.1%), Makaira nigricans (7.3%), Xiphias gladius (17.2%) and Kajikia audax (2.3%). Four of these species could be easily distinguished by COI barcodes but, the striped marlin, K. audax showed high sequence similarity with K. albida and cannot be distinguished by barcodes alone. Control region (889 bp) provided a better phylogenetic signal, consistent with that of the whole mitochondrial genome topology. The stock status plots of billfishes depicted that, all the species were in the developing and exploited phase. Growth, mortality and exploitation rates estimated for four billfishes indicated that the present fishing rates and biomass levels are at safe levels and there is considerable scope for enhancing their fishery. Keywords: CO1 barcodes, Exploitation rate, Large pelagics, Life history, Stock status plots